Penerapan Models Cooperative Learning Tipe Team Games Tournament (TGT) untuk Meningkatkan Keaktifan Siswa pada Mata Pelajaran Al-Qur'an Hadis Kelas V B di Mi Daarul Qur'an - Alya Nur Fauziyah; Naufal Rafif Agustian; Muthia Robiaturrifa; M Makbul; Al Fajar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to enhance the engagement of class V B students at MI Daarul Qur'an in the Al-Qur'an Hadith subject through the implementation of the Team Games Tournament (TGT) cooperative learning model. Using Classroom Action Research (CAR) with the Kemmis and McTaggart framework, the research was conducted in two cycles consisting of planning, action, observation, and reflection stages. Data were collected through observations, interviews, and documentation. The findings indicate that the application of the TGT model significantly improves both learning outcomes and student participation. In Cycle I, learning mastery reached 61.11 percent with an average score of 73.96. This increased to 91.67 percent in Cycle I Meeting II, to 95.83 percent in Cycle II Meeting I, and finally to 100 percent in Cycle II Meeting II with an average score of 100. The TGT approach not only enhances academic achievement but also creates a more active, enjoyable, and dynamic learning environment, encouraging better collaboration among students during group activities. Therefore, the use of the Team Games Tournament (TGT) cooperative learning model is proven effective in improving student engagement and learning outcomes in the Al-Qur'an Hadith subject.